The growth pattern and condition factors of three spot gourami Trichopodus trichopterus (Pallas, 1770) from the Lempake Dam, East Kalimantan - Jusmaldi Jusmaldi; Ardana Reswari Dianingrum; Nova Hariani (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
The growth pattern and condition factors of three spots gourami Trichopodus trichopterus (Pallas, 1770) from Lempake Dam, East Kalimantan, are not yet informed. These studies aimed to investigate fishes' length and body weight, sex ratio, length-bodyweight relationships, growth patterns, and condition factors. The collection of fish sampling was carried out monthly from February to May 2020. A total of 912 individual samples of sepat rawa fish were caught by 15 fish traps using a purposive sampling method at three stations. This research showed that the total length of the fishes analyzed ranged from 31.68 to 103.53 mm, while body weight ranged from 1.12 to 7.22 g. The sex ratio in males and females was 1:1.19. The regression model of the length-body weight relationships calculated was W=3x10-5L2.861 for total samples, W=5x10-5L2.710 for males, and W=2x10-5L2.977 for females. The length-body weight was obtained strong relationships in all samples and sexes, with the regression coefficient (r) ranging from 0.965 to 0.977. An isometric growth pattern and the growth coefficient “b”=2.977 was observed in females, while a negative allometric growth pattern in males and both sexes, with the growth coefficient “b”= 2.710 and “b”=2.861. The values of relative condition factor (Kn) observed for females were ranged from 1.472 to 1.555 and for males ranged from 1.024 to 1.082. The growth pattern and relative condition factor of three spot gourami in the Lempake Dam were affected by the number of fishes in gonad mature condition and body shape. Abstrak Pola pertumbuhan dan faktor kondisi ikan sepat rawa Trichopodus trichopterus (Pallas, 1770) dari Bendungan Lempake, Kalimantan Timur belum pernah diinformasikan. Penelitian ini bertujuan untuk menganalisis panjang dan bobot tubuh ikan, nisbah kelamin, hubungan panjang-bobot tubuh, pola pertumbuhan dan faktor kondisi. Sampel ikan sepat rawa dikoleksi setiap bulannya dimulai dari bulan Februari hingga Mei 2020. Total 912 individu sampel ikan sepat rawa ditangkap dengan 15 perangkap ikan menggunakan metode purposive sampling pada tiga stasiun. Hasil dari penelitian ini menunjukkan panjang total ikan yang dianalisis berkisar antara 31,68-103,53 mm dan bobot tubuh berkisar antara 1,12-17,22 g. Nisbah kelamin jantan dan betina adalah 1:1,19. Model regresi hubungan panjang-bobot tubuh yang dihitung adalah W=3x10-5L2,861 untuk keseluruhan sampel, W=5x10-5L2,710 untuk jantan dan W=2x10-5L2,977 untuk betina. Hubungan panjang-bobot tubuh didapatkan sangat kuat pada keseluruhan sampel ikan dan jenis kelamin, dengan nilai regresi (r) berkisar dari 0,965-0,977. Pola pertumbuhan isometrik dengan koefisien pertumbuhan “b”=2,977 diamati pada betina, sedangkan pola pertumbuhan allometrik negatif pada jantan dan gabungan kedua jenis kelamin, dengan koefisien pertumbuhan “b”= 2,710 dan“b”=2,861. Nilai faktor kondisi relatif (Kn) yang diamati pada betina berkisar antara 1,472-1,555 dan jantan berkisar antara 1,024-1,082. Pola pertumbuhan dan faktor kondisi relatif ikan sepat rawa dari perairan Bendungan Lempake dipengaruhi oleh jumlah ikan kondisi matang gonad dan bentuk tubuh.